Technological conditions effect on structural perfection of Cd₁₋ₓMnₓTe crystals - Shafranyuk, V.; Dremlyuzhenko, S.; Solodin, S.; Fochuk, P. (Functional Materials, 2017)
Dependence of Cd₁₋ₓMnₓTe crystals' quality (0.02<x≤0.55) on synthesis duration and growing conditions, using the complementary X-ray diffraction methods, has been investigated. The obtained experimental results about the structural perfection and types of defects, their distribution and reasons of formation, allowed us to optimize the technological parameters of the perfect crystals' synthesis and growth.